METODOLOGIA KRZEWIENIA DUCHOWOŚCI KOMUNII W ŚWIETLE NOVO MILLENNIO INEUNTE I LISTU JANA PAWŁA II DO KAPŁANÓW NA WIELKI CZWARTEK 2005 - Biela, Bogdan (Studia Pastoralne, 2023)
At the close of the Great Jubilee of the Year 2000 in his letter Novo millennio ineunte John Paul II pointed at pastoral priorities and paths to follow (compare: NMI 29-41) to make the Church the home and the school of communion. He issued a strong warning against the temptation of activism: “Before making practical plans, we need to promote a spirituality of communion […]. Let us have no illusions: unless we follow this spiritual path, external structures of communion will serve very little purpose. They would become mechanisms without a soul, ‘masks’ of communion rather than its means of expression and growth” (NMI 43). It follows that promoting the spirituality of communion should be “the guiding principle of education wherever individuals and Christians are formed, wherever ministers of the altar, consecrated persons, and pastoral workers are trained, wherever families and communities are being built up” (NMI 43). According to the pastoral priorities defined by the Pope, the perspective of sainthood can be related to the attitude of “believing”; the priority of prayer can be associated with “remembering”; the sacrament of reconciliation with “forgiving”; listening to the word of God with “receiving”; Eucharist with “giving thanks”; the priority of grace with “giving”; preaching the word of God with “going out”. Similarly, following the suggestion made by John Paul II, a tool to implement the spirituality of communion can be “a formula of life” hidden in the words of the consecration: “to take bread in one’s hand” is to let the Holy Spirit lead us especially in prayer; “saying the blessing” means to listen; “broke” means to be purified; “giving bread away” means to evangelize; “this is my Body” means to create communion; “take this, all of you, and eat of it” means to spread mercy; “do this in memory of me” means to love by the love of Christ and in the power of the Spirit of God. Following the said attitudes, we have become promoters of the spirituality of communion on the basis of which we are able “to make the Church the home and the school of communion” (NMI 43).